Assessing risk factors and their relationships in enterprise resource planning (ERM) post-implementation [electronic resource] - Usman Musa Zakari Usman, 1984- (2012)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2012